-5(w+3)=6w-5+2(2w+1)

Simple and best practice solution for -5(w+3)=6w-5+2(2w+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(w+3)=6w-5+2(2w+1) equation:



-5(w+3)=6w-5+2(2w+1)
We move all terms to the left:
-5(w+3)-(6w-5+2(2w+1))=0
We multiply parentheses
-5w-(6w-5+2(2w+1))-15=0
We calculate terms in parentheses: -(6w-5+2(2w+1)), so:
6w-5+2(2w+1)
determiningTheFunctionDomain 6w+2(2w+1)-5
We multiply parentheses
6w+4w+2-5
We add all the numbers together, and all the variables
10w-3
Back to the equation:
-(10w-3)
We get rid of parentheses
-5w-10w+3-15=0
We add all the numbers together, and all the variables
-15w-12=0
We move all terms containing w to the left, all other terms to the right
-15w=12
w=12/-15
w=-4/5

See similar equations:

| 30=5/7x | | 3w-24=5w | | 5=11-3c | | 8g-8=1g+8 | | x3−4.1=9.7$ | | 10=22(.87)^x | | 28125*x=375000 | | 5+3(2x-1)=-2(5x-6)+4x | | 3w=6w+5 | | -18+32r=18 | | 1/x=x/3 | | -7(z+6)=49 | | 20=18-x/2 | | 69x=61x | | 20=18–xx/2 | | y/8+40=43 | | 3x+15+55+90=180 | | 3x/18×2x/18=10 | | 3x+-2(3x+2)=8 | | 21x+32=98 | | -3.5=r-8.3 | | −13x−2=−10x−2 | | 3=2b−3 | | 9x+35+90=180 | | 26−10b=-14 | | -8x-2(2-3x)+6-6(4-8x)=13(4x+9)-4(5x-2)+10 | | x+12+58+90=180 | | 14x-84=-1x-1 | | 3x-7=154 | | 20=18–x2 | | 4z−3=13 | | x-100=-9 |

Equations solver categories